Effects of Temperature and pH on the Oxidative Stress of Benthic Marine Invertebrates - González Durán, E.; Cuaya, M. Popoca; Gutiérrez, M. Valencia; León, J. Ancona (Biology bulletin of the Russian Academy of Sciences, 2018)
The impacts that environmental conditions generate on the physiological performance of benthic marine invertebrates are specific and involve several levels of structural organization. The central component is related to the perception of temperature, which in turn produces the dissipation of oxygen in the mitochondria and triggers oxidative stress. Several studies have evaluated the effect of temperature on oxidative stress, however, few studies have examined their interaction with other environmental factors. This review analyzes the results of antioxidant activity that have been reported for benthic marine invertebrates, considering the combined effects of temperature and pH. The evidence shows that the activity increases with the reduction of pH and that the differences between the optimal values and the exposure define the scope of the responses. The results are used to suggest a generalized pattern of the mechanism and discuss the hypotheses that have been proposed to explain the interaction of temperature and pH on stress oxidative response.